Borilne veščine kot prisilno sredstvo v policiji - Markelj, Primož (Šport (Ljubljana), 2014)
To ensure compliance with the legislation and regulations and to perform their job in accordance with the law, a policeman must use in their work specific coercive measures in some situations so as to force the person who resists, attacks or refuses to follow a legitimate order to submit to that their demands. Policemen use several types of authorisations in their work, including coercive measures. They use such measures to act directly on people, which is why care should be taken that nobody is hurt or maltreated. Coercive measures are classified from the mildest (handcuffs and other restraining means) to the most oppressive (firearms).
Keywords: borilne veščine; borilni športi; coercive measures; combat sports; martial arts; physical force; police; policija; prisilna sredstva; samoobramba; self-defence; sport; šport; športna dejavnost; telesna sila; training; usposabljanje